2017
DOI: 10.1140/epja/i2017-12371-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward a complete theory for predicting inclusive deuteron breakup away from stability

Abstract: We present an account of the current status of the theoretical treatment of inclusive (d, p) reactions in the breakup-fusion formalism, pointing to some applications and making the connection with current experimental capabilities. Three independent implementations of the reaction formalism have been recently developed, making use of different numerical strategies. The codes also originally relied on two different but equivalent representations, namely the prior (Udagawa-Tamura, UT) and the post (Ichimura-Aust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 68 publications
2
68
0
Order By: Relevance
“…Spin-parity dependent cross section are calculated for the angles covered in the experiment within the Green's Function Transfer formalism described in Ref. [45,46]. The neutron-nucleus interactions are modeled by the dispersive optical model potential (OMP) of Capote et al [47] implemented through potential no.…”
Section: Corrections Due To Spin-parity Mismatchmentioning
confidence: 99%
“…Spin-parity dependent cross section are calculated for the angles covered in the experiment within the Green's Function Transfer formalism described in Ref. [45,46]. The neutron-nucleus interactions are modeled by the dispersive optical model potential (OMP) of Capote et al [47] implemented through potential no.…”
Section: Corrections Due To Spin-parity Mismatchmentioning
confidence: 99%
“…In the range of energies explored here, however, differences remain of the order of 10% or less, which seems to explain the success of the DWBA to account for experimental data [31,[42][43][44].…”
mentioning
confidence: 86%
“…Due to the short lifetimes involved, direct measurements are currently not possible, and thus indirect methods using (d,p) reactions have been used for both the direct capture [1,2] as well as the compound [3] components. A recent review on (d,p) reactions and its connection to neutron capture can be found in [4]. In addition, single neutron transfer (d,p) reactions can be used to constrain proton capture cross sections, due to mirror symmetry (e.g., [5]).…”
Section: Introductionmentioning
confidence: 99%